Effect of octenyl succinic anhydride modified starch on soy protein-polyphenol binary covalently linked complexes - Dong, Die; Geng, Tenglong; Cui, Bo; Yuan, Chao; Guo, Li; Zhao, Meng; Zou, Feixue; Liu, Pengfei; Zhang, Hongxia (Frontiers in Nutrition, 2023)
The present study aimed to investigate the effects of octenyl succinic anhydride modified starch (OSAS) on soy protein (SP)-(−)-epigallocatechin-3-gallate (EGCG) binary covalently linked complexes. Mean diameters of OSAS-SP-EGCG complexes decreased from 379.6 ± 54.9 nm to 272.7 ± 47.7 nm as the OSAS-to-SP-EGCG ratio changed from 1:2 to 4:1, while ζ-potential decreased from -19.1 ± 0.8 mV to -13.7 ± 1.2 mV. Fourier transform infrared spectroscopy results revealed that the characteristic peaks at 1725 cm−1 and 1569 cm−1 for OSAS disappeared in the OSAS-SP-EGCG complexes, indicating an interaction between OSAS and SP-EGCG complexes. X-ray diffraction analysis showed that with the increase of OSAS content, the diffraction peak at approximately 8.0° decreased from 8.22° to 7.74°, implying that the structures of OSAS and SP-EGCG complexes were rearranged after forming into OSAS-SP-EGCG complexes. The contact angle of the OSAS-SP-EGCG complexes significantly increased from 59.1° to 72.1° with the addition of OSAS increased, revealing that the addition of OSAS improved hydrophobicity of the SP-EGCG complexes. Transmission electron microscopy images revealed that the individual OSAS-SP-EGCG complexes became smaller but stuck together to form large fragments, which was different from the morphology of OSAS and SP-EGCG complexes.Thus, the OSAS-SP-EGCG complexes developed in this study may be effective emulsifiers for improving the stability of emulsion systems in the food industry.